PODO: Trial Design: Phase 2 Study of PF-06730512 in Focal Segmental Glomerulosclerosis - Laurence H. Beck, Jr.; Stephen P. Berasi; J. Brian Copley; Donal Gorman; Daniel I. Levy; Chay Ngee Lim; Joel M. Henderson; David J. Salant; Weining Lu (Kidney International Reports, 2021)
Introduction: Focal segmental glomerulosclerosis (FSGS) is characterized by proteinuria and a histologic pattern of glomerular lesions of diverse etiology that share features including glomerular scarring and podocyte foot process effacement. Roundabout guidance receptor 2 (ROBO2)/slit guidance ligand 2 (SLIT2) signaling destabilizes the slit diaphragm and reduces podocyte adhesion to the glomerular basement membrane (GBM). Preclinical studies suggest that inhibition of glomerular ROBO2/SLIT2 signaling can stabilize podocyte adhesion and reduce proteinuria. This clinical trial evaluates the preliminary efficacy and safety of ROBO2/SLIT2 inhibition with the ROBO2 fusion protein PF-06730512 in patients with FSGS. Methods: The Study to Evaluate PF-06730512 in Adults With FSGS (PODO; ClinicalTrials.gov identifier NCT03448692), an open-label, phase 2a, multicenter trial in adults with FSGS, will enroll patients into 2 cohorts (n = 22 per cohort) to receive either high- or low-dose PF-06730512 (intravenous) every 2 weeks for 12 weeks. Key inclusion criteria include a confirmed biopsy diagnosis of FSGS, an estimated glomerular filtration rate (eGFR) ≥45 ml/min/1.73 m2 based on the Chronic Kidney Disease Epidemiology Collaboration formula (30–45 with a recent biopsy), and urinary protein-to-creatinine ratio (UPCR) >1.5 g/g. Key exclusion criteria include collapsing FSGS, serious/active infection, ≥50% tubulointerstitial fibrosis on biopsy, and organ transplantation. The primary endpoint is change from baseline to week 13 in UPCR; secondary endpoints include safety, changes in eGFR, and PF-06730512 serum concentration. Results: This ongoing trial will report the efficacy, safety, pharmacokinetics, and biomarker results of PF-06730512 for patients with FSGS. Conclusion: Findings from this proof-of-concept study may support further development and evaluation of PF-06730512 to treat FSGS and warrant assessment in phase 3 clinical trials.